How Does Tourism Contribute to Happiness? Evidence of The Role of Hotels and Accommodation in Sumatera - Triananda, Silva; Aulia, Deswira; Tri Purwaningsih, Vitriyani; Suparta, I Wayan; Aida, Neli (Jurnal Ekonomi Pembangunan, 2024)
Happiness is the ultimate goal of a prosperous life that a person wants to achieve. There are many stigmas and opinions about measuring happiness, such as happiness seen from health, work, education, family harmony, and more. With so many ways to see and measure happiness, a happiness index was created to measure the welfare and happiness of people in a region or country. This research aims to test and analyze the influence of tourism on happiness by using the number of hotels and accommodations, technology and information, health, consumption expenditure, education, and crime. The data used is secondary data, with a population of 10 provinces on the island of Sumatra. The analysis technique used is Panel Data Regression Analysis. The research results show that tourism, technology, health, and consumption expenditure positively affect the happiness index. In contrast, education and crime have a negative effect on the happiness index in 10 provinces on the island of Sumatra